Design of a Quadcopter Drone for Firefighting Support - Gaguk Marausna; Muhammad Faiz Alfatih; Setia Budi Islami (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
Fires in densely populated areas are often difficult to handle due to limited access for firefighting vehicles, especially in narrow alleys. This research designs and tests a quadcopter drone as a solution to help the firefighting process in hard-to-reach areas. The drone was designed using a polyamide fiberglass F450 frame, Sunnysky 1250kv brushless motor, 10-inch propeller, 2200 mAh LiPo battery, and Pixhawk control system. The research method involves 3D design, component assembly, and testing the drone's performance against power consumption with and without load. The test results showed that the drone was able to fly stably with a lift of up to 5.3 kg and a flight duration of 45 minutes and was able to carry a sprayer with a hose length of 7 meters. Average battery consumption was in the range of 47–57% per 5 minutes, depending on the load. The drone proved effective in assisting firefighting in areas with limited access.